Booms and busts in Latin America: The role of external factors - Alejandro Izquierdo; Randall Romero; Ernesto Talvi (Inter-American Development Bank, Research Department, 2008)
This paper analyzes the relevance of external factors in average quarterly GDP growth for 1990-2006 in the seven largest Latin American countries (LAC7). Modeling the relationship between LAC7 GDP and several external factors, it is found that those factors account for a significant share of variance in LAC7 GDP growth, and that external shocks produce significant responses. Likewise, a significant share of recent LAC7 growth performance can be explained by an external factor 'tailwind'. Also evaluated is the impact of deterioration in external financial conditions. Finally, the relevance of these findings for policy evaluation is emphasized. Growth performance, the strength or weakness of macroeconomic fundamentals and the impact of domestic macro and micro policies on growth can only be properly appraised by first filtering out the effects of external factors.
Keywords: F31; F32; F34; F41; 330; External Factors; Business Cycle; Growth; Sudden Stops; Terms of Trade; Latin America